Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Love Of Money Terhadap Perilaku Etis Mahasiswa Akuntansi - Syahgiffa Aulia Putri; Fera Sriyunianti; Ria Angriani (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the influence of intellectual intelligence, emotional intelligence, and love of money on the ethical behavior of accounting students. The research method used is a quantitative approach. The population in this study were accounting students from the 2021 and 2022 intakes of Padang State Polytechnic. This study used primary data collected by distributing questionnaires via Google Forms using a purposive sampling technique, resulting in 119 respondents. The data analysis method used multiple linear regression with IBM SPSS Statistics 25 software. The results show that intellectual intelligence and emotional intelligence partially influence the ethical behavior of accounting students, while love of money does not. Simultaneously, intellectual intelligence, emotional intelligence, and love of money influence the ethical behavior of accounting students.